Stem cell models of adipogenesis: modulating temperature to promote MSC-derived beige adipocytes - Lugo Leija, Hilda Anaid (2020)
Since the discovery of brown adipose tissue (BAT), emerging strategies to promote its activation and recruitment have been examined due to the thermogenic capacity of BAT, which makes it an encouraging approach to regulate obesity and related diseases. Uncoupling protein 1 (UCP1) is a specific protein located in the inner mitochondria of brown adipocytes, when activated, uncouples substrate oxidation from ATP production by dissipating energy in the form of heat. Beige adipocytes have been recently discovered and are cells which possess the morphological and biochemical characteristics of brown adipocytes, including UCP1. It has been previously reported that human BAT expresses beige cell-selective genes instead of classical brown markers which underline the importance of understanding beige adipogenic differentiation, induction and maintenance. All adipocytes share a mesodermal origin. Mesenchymal stem cells (MSCs) are able to differentiate into a variety of lineages, including adipocytes. To date, the most potent stimulus to activate UCP1 in BAT is cold exposure. However, whether cells sense temperature and differentiate into brown and beige lineages is not fully understood. The aim of this thesis is to obtain a better understanding on how low temperature affects the differentiation of MSCs into white, beige and brown adipocytes and if these traits acquired are maintained after being switched to normal culture conditions (37ºC). Additionally, cold exposure evaluation during adipogenic differentiation of human MSCs derived from cord tissue taken from diabetic and healthy pregnancies at term were examined. Cold temperature (32ºC) was investigated for its potential to activate browning in adipocytes. Here, MSCs differentiated under normal culture conditions showed a dual leptin and UCP1 protein expression in the majority of differentiated cells. Hypothermic conditions applied while the MSCs were under adipogenic differentiation promoted a brown/beige morphological and molecular signature. These changes were accompanied with enhanced UCP1 protein abundance, uncoupled respiration and metabolic adaptation. Hypothermic differentiated cells showed a marked translocation of leptin into adipocyte nuclei, which indicates a potential role for leptin in the browning process. These results indicated that MSCs could be driven to form beige like adipocytes by differentiating them in a cold environment.